An American color : race and identity in New Orleans and the Atlantic world - Wegmann, Andrew N. (Race in the Atlantic world, 1700-1900., 2022)
"For decades, scholars have used the coastal city of New Orleans as a remarkable outlier, an exception to nearly every 'rule' of accepted U.S. historiography. American only by adoption, New Orleans, in the vast majority of studies, serves as a frontier town of the circum-Caribbean, a vestige of North America's European colonial era along the southern coast of a foreign, northern, insular United States. Perhaps more than any other topic, then, race has served as a singular identifier for New Orleans and its perceived exotic culture. Indeed, part of its appeal, it seems, was its so-called 'three-tiered caste system' placing free people of color between whites and slaves on a broad social and even political hierarchy. Beneath that, too, many studies have argued, a complex algorithm of racial mixtures was at work well into the 19th century, a complexity of racial understanding and treatment that almost every scholar to date has claimed simply did not exist within the more 'American' states further north and outside the bounds of the Caribbean's bizarre socio-racial influence. The reality, as An American Color explains, is that on the surface, New Orleans did have a racial and social system that confounded the more prudent and established black-white binary at work in the social rhetoric of the British-descended states further north. But this was not unique, especially within the United States. As the manuscript argues, New Orleans is representative not of a place added to the United States from a distinct and foreign culture but instead is representative of a place with different words for the same practices found throughout the North American continent and indeed the Atlantic World. The racial system found in New Orleans, seemingly open and ill-defined compared to the strict black-white split of the United States, was not foreign at all. In fact, throughout the U.S. Atlantic South, from New Orleans to Charleston to Richmond and back again, the social practice of race remained constant and Atlantic in nature, predicated on a complex, socially-infused, multi-tier system of proscribed racial value that combined wealth, skin tone, ancestry, local reputation, and civil service into a single, nameless process that challenged and sometimes abandoned preordained definitions of 'black' and 'white' for an assortment of fluid but meaningful designations in between. In New Orleans, the United States did not find its first introduction to the Atlantic socio-racial system. It simply received a more varied language for what it already had and could (or would) never define. At its core, then, this project uses New Orleans as an entry point for the study of an Atlantic United States rather than the opposite, which has come to define the city's academic use in studies of the 18th and 19th centuries. Focusing initially on the foundation of New Orleans and the development and evolution of its seemingly unique free community of color and the racial language that came to define it over the course of two European colonial regimes, the manuscripts draws the early 19th-century United States into a narrative context in which rarely appears-namely, that of colonial Central America, the Caribbean, West Africa, and continental Europe. By centering the narrative on the growth of New Orleans from French colonial outpost to Spanish trading town to American riverine metropolis on the eve of the American Civil War, this project shows that New Orleans, rather than the more common United States, joined a nation in 1803 to which it was not socially and racially foreign and with which it shared an abundance of socio-racial practices separated only by a lack of common language and public definition"--